Adverse Events Among Hospitalized Critically Ill Patients: A Retrospective Cohort Study. Issue 1 (January 2020) - Sauro, Khara M.; Soo, Andrea; Quan, Hude; Stelfox, Henry T.
Abstract : Objective: The objective of this study was to estimate the frequency and type of adverse events (AEs) among critically ill patients and identify patient and hospital factors associated with AEs and clinical and health care utilization consequences of AEs. Materials and Methods: This retrospective cohort study includes patients admitted to 30 intensive care units (ICUs) in Alberta, Canada from May 2014 to April 2017. The main outcome was AEs derived from validated ICD-10, Canadian code algorithms for 18 AEs. Estimates of the proportion and rate of AEs are presented. The association between documented AEs and patient (eg, age, sex, comorbidities) and hospital (eg, ICU site and type, length of stay, readmission) variables are described using regression methods. Results: Of 49, 447 hospital admissions with admission to ICU, ≥1 AEs were documented in 12, 549 (25%) admissions. The most common AEs were respiratory complications (10%) and hospital-acquired infections (9%). AEs were associated with having ≥2 comorbidities [odds ratio (OR)=1.4, 95% confidence interval (CI)=1.3–1.4], being admitted to the ICU from the operating room or another hospital ward (OR=1.8, 95% CI=1.7–2.0 and OR=2.7, 95% CI=2.5–3.0, respectively) and being readmitted to ICU during their hospital stay (OR=4.8, 95% CI=4.7–5.6). Patients with an AE stayed 5.4 days longer in ICU (95% CI=5.2–5.6 d, P <0.001), 18.2 days longer in hospital (95% CI=17.7–18.8 d, P <0.001) and had increased odds of hospital mortality (OR=1.5, 95% CI=1.4–1.6) than those without an AE. Conclusions: AEs are common among critically ill patients and certain factors are associated with AEs. Documented AEs are associated with longer stays and increased mortality. Abstract : Supplemental Digital Content is available in the text.